The theosophical enlightenment - Godwin, Joscelyn (SUNY series in Western esoteric traditions., 1994)
An enticing intellectual history of various esoteric currents from the early Romantic period to the early twentieth century. The author maintains that the Theosophical Society held a crucial position as the place where all those currents temporarily united, before diverging again.